Stress Modulates Illness-Course of Substance Use Disorders: A Translational Review - Lijffijt, Marijn; Hu, Kesong; Swann, Alan C. (Frontiers in Psychiatry, 2014)
Childhood trauma and post-childhood chronic/repeated stress could increase the risk of a substance use disorder by affecting 5 stages of addiction illness-course: (a) initial experimentation with substances; (b) shifting from experimental to regular use; (c) escalation from regular use to abuse or dependence; (d) motivation to quit; (e) risk of (re-)lapse. We reviewed the human literature on relationships between stress and addiction illness-course. We explored per illness-course stage (i) whether childhood trauma and post-childhood chronic/repeated stress have comparable effects, and (ii) whether effects cut across classes of substances of abuse. We further discuss potential underlying mechanisms by which stressors may affect illness-course stages for which we relied on evidence from studies in animals and humans. Stress and substances of abuse both activate stress and dopaminergic motivation systems, and childhood trauma and post-childhood stressful events are more chronic and occur more frequently in people who use substances. Stressors increase risk to initiate early use potentially by affecting trait-like factors of risk-taking, decision making, and behavioral control by diminished prefrontal functioning. Stressors also accelerate transition to regular use, potentially due to prior effects of stress on cross-sensitization of dopaminergic motivation systems with substances of abuse, especially in people with high trait impulsivity who are more prone to sensitization. Finally, stressors increase risk for abuse and dependence, attenuate motivation to quit, and increase relapse risk, potentially by intensified sensitization of motivational systems, by a shift from positive to negative reinforcement due to sensitization of the amygdala by corticotropin releasing factor, and by increased sensitization of noradrenergic systems. Stress generally affects addiction illness-course across childhood stressor types, and across classes of substances of abuse.